2021
DOI: 10.1057/s41599-021-00877-9
|View full text |Cite
|
Sign up to set email alerts
|

Parenting by lying in Turkey: associations with negative psychosocial outcomes and psychopathy in adulthood

Abstract: Parenting by lying—a practice whereby parents lie to their children as a means of emotional or behavioral control—is common throughout the world. This study expands upon the existing, albeit limited, research on parenting by lying by exploring the prevalence and long-term associations of this parenting practice in Turkey. Turkish university students (N = 182) retrospectively reported on their experiences of parenting by lying in childhood, their current frequency of lying towards parents, their present level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Although few parents are aware of the dangers of parenting by lying, the results of this study found a significant association between parenting by lying about money and adolescent mobile phone addiction. Along with previous studies on the negative effects of parenting by lying ( Liu and Wei, 2020 ; Setoh et al, 2020 ; Jackson et al, 2021 ; Wei and Liu, 2021 ), we consider it meaningful to draw more attention to the negative outcomes of parenting by lying. Furthermore, with the prevalence of smart phones, mobile phone addiction is increasingly developing into a major problem in both family and school education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few parents are aware of the dangers of parenting by lying, the results of this study found a significant association between parenting by lying about money and adolescent mobile phone addiction. Along with previous studies on the negative effects of parenting by lying ( Liu and Wei, 2020 ; Setoh et al, 2020 ; Jackson et al, 2021 ; Wei and Liu, 2021 ), we consider it meaningful to draw more attention to the negative outcomes of parenting by lying. Furthermore, with the prevalence of smart phones, mobile phone addiction is increasingly developing into a major problem in both family and school education.…”
Section: Discussionmentioning
confidence: 99%
“…However, parents often lie to their children during parenting, believing that lying is acceptable in certain situations ( Heyman et al, 2009 ). Although parents may barely connect parenting by lying with any negative consequences to children, it is demonstrated to be positively associated with children’s internalization and externalization issues in adolescence and adulthood ( Santos et al, 2017 ; Liu and Wei, 2020 ; Setoh et al, 2020 ; Jackson et al, 2021 ; Wei and Liu, 2021 ). Given that mobile phone addiction is a typical problem of externalization in the digital age, we assume that parenting by lying may be positively associated with mobile phone addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Additional research conducted with Turkish college students found that almost all (96%) reported that their parents engaged in this practice ( Jackson et al, 2021). These rates are comparable to reports of Asian participants (100%; Setoh et al, 2022) but higher than those of European Americans (78%; .…”
Section: What Factors Are Predictive Of Parenting By Lying?mentioning
confidence: 63%
“…1, path 2) has been supported by the existing evidence. It has been found that exposure to parenting by lying was significantly associated with poorer psychosocial outcomes, such as externalizing problems, internalizing problems, psychopathy, lying behavior, and less prosociality (e.g., Dodd & Malm, 2021;Jackson et al, 2021;Low et al, 2023). Darling and Steinberg (1993) highlighted the importance of parent-child relationships in moderating the pathway between parenting practices and child outcomes (Fig.…”
Section: A Theoretical Framework Of Parenting By Lyingmentioning
confidence: 99%
“…Contrasted to Factor 1 psychopathy, Factor 2 psychopathy is more strongly affected by childhood abuse (Moreira et al, 2020). A further study (Jackson et al, 2021) also found parenting by lying -i.e., controlling the child emotionally and behaviourally through lying to them -to be uniquely associated with Factor 2 psychopathy.…”
Section: Etiology and Origins Of The Vulnerable Dark Triadmentioning
confidence: 82%